Influence of fertigation regimes on yield and fruit quality of grapefruit under Khartoum State conditions, Sudan - Khalifa, Ahmed; Hamed, Ibtihal; Ahmed, Shaker; Ali, Mohamed; Ali, Imad-eldin; Heng, Lee; Dawoud, Dawoud (Gezira Journal of Agricultural Science, 2018)
The experiment was conducted in a private orchard at Tayba Alhasnab area, Khartoum, Sudan, during 2016 and 2017 to evaluate the influence of fertigation regimes on yield and yield components of foster grapefruit under Khartoum State conditions. Four treatments viz 50%, 75%, 100% and 125% of urea recommended dose were applied by fertigation. The experiment was laid out in randomized complete block design with three replicates and each plot encompassed 2 trees. Results revealed that fertigation regimes had significant effects on number of fruits per tree and total yield. The highest yield and number of fruits per tree were obtained by 125% of urea recommended dose. The highest leaf nitrogen concentrations were obtained with 125% of urea recommended dose while the lowest was obtained for 50% of urea recommended dose in both years. Moreover, the highest partial factor productivity was obtained with 50% of urea recommended dose and the lowest with 125% of urea recommended dose.         أجريت التجربة في بستان خاص في منطقة طيبة الحسناب جنوب الخرطوم، السودان، خلال الفترة من 2016  وحتي 2017 لتقييم اثر جرعات التسميد مع الري علي انتاجية وجودة القريب فروت فوستر تحت ظروف ولاية الخرطوم. اربع معاملات هي 50% و 75% و 100% و 125% من جرعة اليوريا الموصي بها تم تطبيقها بالتسميد مع الري. التجربة تم تصميمها بنظام القطاعات العشوائية الكاملة من اربعة مكررات وشملت كل قطعة شجرتين. أظهرت النتائج أن جرعات التسميد مع الري قد اثرت معنويا علي عدد الثمار في كل شجرة والانتاجية الكلية في كلا الموسمين. اعلي انتاجية وعدد ثمار في الشجرة  تم الحصول عليها مع 125% من جرعة اليوريا الموصي بها. اعلي تركيز للناتروجين في الاوراق تم الحصول عليه مع 125% من جرعة اليوريا الموصي بها واقل تركيز عند 50% من جرعة اليوريا الموصي بها في العامين. علاوة علي ذلك معامل الانتاجية الجزئي كان اعلي عند 50% من جرعة اليوريا واقل مع 125% من جرعة اليوريا الموصي بها في العامين.